2018
DOI: 10.1037/lat0000093
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Latina/o youth’s internal health locus of control, cultural factors, and body mass index.

Abstract: Compared to their peers, Latina/o youth are at high risk of being overweight and obese and experiencing related health problems. Because of this, it is important to identify factors that may contribute to obesity among Latina/o youth. We explored the relationships among internal health locus of control (IHLOC), cultural factors (cultural orientation, ethnic identity), and Latina/o adolescents' body mass index (BMI; an index of obesity and overweight). One hundred twenty-eight Latina/o adolescents (ages 13-18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(94 reference statements)
2
4
0
Order By: Relevance
“…Furthermore, adolescent LOC showed significant correlation with obesity from age 13. These finding are in line with the results of the study performed by Radcliff et al among Latina youths [24]. In this study, higher participant IHLC was associated with lower BMI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, adolescent LOC showed significant correlation with obesity from age 13. These finding are in line with the results of the study performed by Radcliff et al among Latina youths [24]. In this study, higher participant IHLC was associated with lower BMI.…”
Section: Discussionsupporting
confidence: 93%
“…However, the results of the analysis of the relationship between MHLC scores and healthy lifestyle behaviors are variable. A significant association was reported for MHLC and dietary patterns [23], body mass index (BMI) [24], quality of life in patients with diabetes [25], the effect of organic food label on food consumption [26], compliance with childhood vaccinations [27], self-assessed health [28], cyberbullying and being victimized [29], and even for mortality [30]. The studies performed in Polish populations revealed a significant association between IHLC and health behaviors, including health nutrition, physical activity and using safety belts in cars, in students of health sciences [31], between PHLC and health behaviors in medical workers [32], and between IHLC, PHLC, and health behaviors in adults from other professional groups [32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the Internal Dimension is a predictor of successful obesity treatment; people with high internal control achieve more weight reduction and tend to maintain it longer, compared to the group with a dominant External Dimension. Meanwhile, overweight and obese individuals are more likely to have an external health locus of control [ 123 , 124 ]. Conversely, it has been observed that by knowing a patient’s attitude toward health control, obesity treatment programs can be adapted to their individual preferences, which will lead to greater satisfaction and more weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The MEIM has demonstrated reliability and validity across ethnic groups (Cheng et al, 2010; Chesin & Jeglic, 2012; Walker et al, 2008). Specifically, the MEIM has shown good psychometric properties among Latinx samples (Radcliff et al, 2018). In the present study, the MEIM demonstrated good reliability (α = .89).…”
Section: Methodsmentioning
confidence: 99%